1999
DOI: 10.1021/ic9810687
|View full text |Cite
|
Sign up to set email alerts
|

An Interpretation of Gated Behavior:  Kinetic Studies of the Oxidation and Reduction Reactions of Bis(2,9-dimethyl-1,10-phenanthroline)copper(I/II) in Acetonitrile

Abstract: Reduction reactions of Cu(dmp)(2)(2+) (dmp = 2,9-dimethyl-1,10-phenanthroline) by ferrocene (Fe(Cp)(2) = bis(cyclopentadienyl)iron(II)), decamethylferrocene (Fe(PMCp)(2) = bis(pentamethylcyclopentadienyl)iron(II)), and Co(bpy)(3)(2+) (bpy = 2,2'-bipyridine) and oxidation reactions of Cu(dmp)(2)(+) by Ni(tacn)(2)(3+) (tacn = 1,4,7-triazacyclononane) and Mn(bpyO(2))(3)(3+) (bpyO(2) = N,N'-dioxo-2,2'-bipyridine) were studied in acetonitrile for the purpose of interpreting the gated behavior involving copper(II) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…Therefore, the kinetic studies with excess reductants and the kinetic studies of the oxidation reactions of such Co(III/II) couples are scarce, although such a study is essential to examine the mechanisms postulated to date, including the gating phenomenon. Recently several nonconcerted ET reactions have been reported in which the innersphere reorganization process takes place before the very fast outersphere ET with minimal outersphere reorganizations (33)(34)(35)(36).…”
Section: Absorption Spectramentioning
confidence: 99%
“…Therefore, the kinetic studies with excess reductants and the kinetic studies of the oxidation reactions of such Co(III/II) couples are scarce, although such a study is essential to examine the mechanisms postulated to date, including the gating phenomenon. Recently several nonconcerted ET reactions have been reported in which the innersphere reorganization process takes place before the very fast outersphere ET with minimal outersphere reorganizations (33)(34)(35)(36).…”
Section: Absorption Spectramentioning
confidence: 99%
“…[10][11][12][13][14] The kinetic results were analyzed by using the following equation derived for the Square Scheme by Rorabacher and co-workers. [10][11][12][13][14] The kinetic results were analyzed by using the following equation derived for the Square Scheme by Rorabacher and co-workers.…”
Section: Under the Conditions Of [Cu(pdt) 2 ] + << [Co(bipy) 3 ] 3+mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] On the other hand, we found that the electron transfer (cross) reactions between different copper complexes and the electron self-exchange reactions are not gated. Single crystal analyses revealed that [Cu(pdt) 2 (H 2 O) 2 ](BF 4 ) 2 was in the D 2h symmetry with two axial water molecules and two symmetrically coordinated equatorial pdt ligands, while the coordination structure of [Cu(pdt) 2 ]BF 4 was a squashed tetrahedron (dihedral angle = 54.87 o ) with an asymmetric coordination by two pdt ligands: one pdt ligand coordinated to Cu(I) through pyridine-N and triazine-N2 while another pdt through pyridine-N and triazine-N4, and a stacking interaction between the phenyl ring on one pdt and the triazine ring on another pdt caused the squashed structure and nonequivalent Cu-N bond lengths.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also widely studied are Cu(II/I) systems containing different polypyridyl ligands: 2,2-bipyridine, 1,10-phenanthroline, and their substituted derivatives [ 24 , 25 , 26 ]. One example is the reduction, which was convincingly shown for the reactions of Cu(II)(diphenyldimethylbipyridine) 2 and Cu(II)(dimethylbipyridine) 2 with ferrocene and decamethylferrocene [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%